Pengembangan Hybrid App Arsip Ijazah dan SKHUN di SMK Pembangunan Bukittinggi - Khomarudin, Agus Nur; Novita, Rina; Aulia, Romy; Putri, Ega Evinda; Jamaluddin, Jamaluddin (INCODING: Journal of Informatics and Computer Science Engineering, 2025)
The importance of fast, precise, and accurate information is highly essential for every institution or organization, particularly in archival management. SMK Pembangunan Bukittinggi is currently making continuous efforts to support the "Innovative Vocational School" program. However, the institution faces several challenges in managing the archiving of diplomas and SKHUN (School Leaving Certificates). The current archiving process is still carried out using conventional methods that are not yet digital-based, which presents several weaknesses, such as the risk of damage, fire, and difficulties in retrieving required documents. This research follows the development steps outlined in the Agile methodology. The research has produced a hybrid application for diploma and SKHUN archiving at SMK Pembangunan Bukittinggi, which has undergone several tests, including system validity testing, which resulted in a score of 0.83, indicating a valid system; practicality testing with a score of 0.90, categorized as very practical; and effectiveness testing with a score of 0.82, indicating high effectiveness. Therefore, it can be concluded that the hybrid archiving application for diplomas and SKHUN developed in this study is feasible to be implemented at SMK Pembangunan Bukittinggi..